Integrating Tradition and Technology: Digital Audio Workstation-Based Learning for Traditional Music Preservation - Saputra, Dani Nur; Cahyono, Agus; Utomo, Udi; Raharjo, Eko; Nainggolan, Oriana Tio Parahita (Resital: Jurnal Seni Pertunjukan, 2024)
The use of technology into conventional music education offers novel prospects for both preservation and creativity. This study examines the application of Digital Audio Workstations (DAWs) as an educational instrument for instructing and conserving traditional music, specifically within the setting of Desa Cisaat, Subang, West Java. The study included 25 young participants from the hamlet, with the objective of evaluating how DAW-based learning may enhance their involvement with traditional Sundanese music. The study illustrates how DAWs connect old musical traditions with contemporary digital approaches through workshops and instructional activities, allowing kids to engage with traditional music in more innovative and accessible manners. The research conducted used a type of qualitative research with a descriptive approach. The data collection techniques used are through observation, interviews, and literature studies. The analysis carried out adopted from miles and huberman where the process includes data collection, data reduction, data presentation, and conclusion. The results indicate that DAW-based learning cultivates creativity, increases student engagement, and facilitates a profound comprehension of musical legacy among younger generations. This technique facilitates the recording, adaptation, and widespread dissemination of traditional music, thus assuring its preservation in the digital era. The study indicates that the integration of tradition and technology via Digital Audio Workstations (DAWs) signifies a viable avenue for the future of music instruction and preservation, especially in rural regions.